The Influence Of Csr Practices On Csr-Hr Capabilities And Organizational Performance Among Malaysian Public Listed Companies - Halim, Muhammad Nazri Abdul (2018)
The issue of social responsibility and how HR plays an important role in executing CSR have become prevalent in the Malaysian government agenda. The combination of HRM in CSR activities is important to be seen as a pioneer and major prerequisite for the realization of national mission and improve the welfare of the society. Corporate bodies should take note that CSR is not just helping and giving back to employees only but covers all responsibilities including community life around. Bursa Malaysia commissioned CSR Asia conducted a CSR survey and analysed a random sample of company responses to give an overall picture of where listed companies in 2007 found that companies received low scores and lag far behind, lacking awareness and understanding of CSR concepts as well as CSR issues relevant to their operations. This study aims at investigating the contribution of the HRM capabilities in driving CSR practices among public listed companies (PLC) in Malaysia towards organizational performance. To achieve the objectives, five key research questions of this study attempt to answer. This study will apply two types of data analysis software namely Partial Least Squares (PLS) with SmartPLS M3 2.0 (2010) and Statistical Package for Social Sciences (SPSS) version 22. Therefore, the sampling frame of this study is derived from the list of 930 public listed companies in Bursa Malaysia. From the analysis, 17 hypotheses that have been tested showed that 9 hypotheses out of 17 hypotheses supported.